Final destination [videorecording (DVD)] - Walker, Shirley, 1945-2006 (New Line platinum series., 2000)
After being kicked off the plane because of his disruptive premonition, Alex and some of his classmates watch as the premonition comes true. Now having dodged death once, the terror begins in full as fate hunts them down one-by-one.